Characteristics of high-quality early childhood education and care: a study from Australia - Phillips, Alicia; Boyd, Wendy (Frontiers in Education, 2023)
The early childhood environment influences a young child’s growth, wellbeing and development, and the young child’s environment determines lifelong outcomes (Heckman, 2013; The Front Project, 2019). The impact of the environment on children’s developing brain capacity has been shown to affect the hard wiring that occurs in the first years of life (Center on the Developing Child, 2023). Brain development in the early years is shaped and formed in response to environmental experiences. The learning environment is established and designed by the early childhood educators - establishing and implementing routines, deciding on the environment and with what equipment, and developing and maintaining relationships with children, families and staff. The Australian Children’s Education and Care Quality Authority (ACECQA) has developed and implemented a national quality standard (NQS) that addresses the quality of the environment in ECEC services. The NQS comprises seven quality areas that early childhood educators implement in these quality outcomes for children. Even though early childhood educators are the key decision-makers in implementing quality learning experience for children their perspectives on the NQS has not been heard. This study provides the early childhood educators’ perspectives of the characteristics of long day care (LDC) centres (for children aged from birth to five years) that they perceived to be important for provision of high-quality ECEC. This paper presents the findings from 15 interviews with early childhood educators regarding their perspectives of what characteristics enabled their LDC centre to be assessed as ‘Exceeding’ the NQS, one of the highest quality ratings possible. Findings indicate that the educators and their qualities in leadership and teamwork were an important characteristic of the LDC centre to provide high-quality ECEC. However, while the educators’ attributes were deemed important it was clear that there was an interconnectedness of factors including the relationships between children, families and educators, the financial capacity, and the governance and structure of the LDC centre, and within the LDC centre that contributed to the provision of high-quality ECEC. Recommendations are made that LDC centres could be incentivised to provide professional learning for staff leadership, teamwork and capability to provide high-quality ECEC.